A combination method of hydrofluoric acid, oxalate and NaOH‐EDTA extractions to determine phosphorus species in soil by 31P‐NMR spectroscopy. (31st August 2016) - Kobayashi, K.; Takamoto, A.; Hashimoto, Y.
Abstract: The objective of this study was to investigate the applicability of selective extraction methods in combination with solution phosphorus‐31 ( 31 P) nuclear magnetic resonance (NMR) for the determination of organic phosphorus (Po ) species in soil. Inositol hexakisphosphates (IHP) and glucose 6‐phosphate (GP) were identified in the soil. IHP adsorbed to both soil organic matter (SOM) and short‐range order (SRO) minerals, whereas GP adsorbed only to SOM. These results suggest that Po hosting phases are different depending on Po species.